Multiple bowel perforation and necrotising fasciitis secondary to abdominal liposuction in a patient with bilateral lumbar hernia - Vincent Dellière; N. Bertheuil; Y. Harnois; S. Thiènot; M. Gèrard; M. Robert; E. Watier (Indian Journal of Plastic Surgery, 2014)
We present a rare complication of abdominal liposuction: bowel perforation and necrotizing fasciitis. Because of bilateral lumbar hernia, a 56-year-old woman had caecum and descending colon perforation during lipoplasty. She had septic shock syndrome at her admission. The authors treated this complex wound with several debridement, omental flap, NPWT and split-thickness skin graft. The incidence of abdominal wall perforation with visceral injury is 14 in 100,000 liposuctions performed. There are only 12 cases of bowel perforation in literature but this complication is probably underestimated. Prompt surgical debridement is absolutely mandatory in this life threatening scenario. Lumbar hernia is very rare and should be ruled out before every abdominal liposuction clinically or with imaging modalities.